2009
DOI: 10.17221/1732-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbohydrates in grass silage-based diets on in sacco ruminal degradability of barley (Hordeum vulgare L. cv. Lomerit) grain ground to different particle sizes

Abstract: The rate and extent of rumen digestion are influenced by the complementarity of the release of N and energy compounds that has an effect on the ruminal microbial population (Rotger et al., 2006). The diet based on grass silage is characterized by a high level of rapidly degraded crude protein, creating an asynchronous relationship between the availability of protein and energy (Givens and Rulquin, 2004). In the meta-analysis of data reporting the true digestibility of N for the gastrointestinal tract AbstrAct:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It is likely that the nutritional synchrony also affects feedstuff degradation in the rumen, but the information describing these relationships is limited. Results from an in sacco study showed that the rumen degradability of barley grain nutrients was influenced by the type of non-fibre carbohydrates included in grass silage-based diets (Niwińska, 2009). There is no information about the effects of plant protein supplements like lupin seeds on in sacco degradability, although the ruminal degradation of feed protein is an essential factor for assessing the feed protein value according to feed evaluation systems for ruminants (Jarrige, 1989;NRC, 2001).…”
mentioning
confidence: 99%
“…It is likely that the nutritional synchrony also affects feedstuff degradation in the rumen, but the information describing these relationships is limited. Results from an in sacco study showed that the rumen degradability of barley grain nutrients was influenced by the type of non-fibre carbohydrates included in grass silage-based diets (Niwińska, 2009). There is no information about the effects of plant protein supplements like lupin seeds on in sacco degradability, although the ruminal degradation of feed protein is an essential factor for assessing the feed protein value according to feed evaluation systems for ruminants (Jarrige, 1989;NRC, 2001).…”
mentioning
confidence: 99%